Hubungan Kualifikasi Akademik dengan Kompetensi Pedagogik Guru RA - Rita Rosita; Helmi Aziz (Jurnal Riset Pendidikan Guru Paud, 2021)
Abstract. This study aims to determine the mapping of the pedagogic competence of RA teachers in Baleendah District, Bandung in terms of academic qualifications and to determine the relationship between the academic qualifications of RA teachers and the Pedagogic Competence of RA teachers in Baleendah District, Bandung. This research uses correlational descriptive quantitative method. The location of this research is the RA Institute (Raudhatul Athfal) in Baleendah District, Bandung Regency. The population in this study were 265 teachers from 55 RA institutions. Then, samples were taken with an error rate of 5% using the Solvin technique, totaling 159 teachers. Data collection techniques used are observation, questionnaires, and documentation. The instrument validation uses the product moment correlation formula and the reliability test uses the Cronbach Alpha formula. The data analysis technique uses categorization techniques for mapping pedagogic competencies in terms of academic qualifications, and Product Moment correlation techniques to find the relationship between the two variables. The results of the descriptive analysis show that teachers who have pedagogic competence in the medium category are 101 teachers (63.5%), 30 teachers (18.9%) in the high category, and 28 teachers (17.6%) in the low category. There is a significant positive relationship between academic qualifications and the pedagogic competence of RA teachers, Baleendah District, Bandung Regency. Based on the results of the study, it can be concluded that the pedagogic competence of RA teachers in Baleendah District, Bandung Regency is in the medium category (63.5%) and there is a significant positive relationship between the academic qualifications of teachers and the pedagogical competence of RA teachers with moderate levels. The suggestions given by the researchers are: to the teachers of the Raudhatul Athfal (RA) institution to improve the pedagogic competence of RA teachers and also to improve their academic qualifications for teachers who are not in accordance with government regulations in order to meet the predetermined academic qualification standards. Abstrak. Penelitian ini bertujuan untuk mengetahui pemetaan kemampuan kompetensi pedagogik guru RA di Kecamatan Baleendah Bandung ditinjau dari kualifikasi akademik dan mengetahui hubungan antara kualifikasi akademik guru RA dengan Kompetensi Pedagogik Guru RA di Kecamatan Baleendah Bandung. Penelitian ini menggunakan metode kuantitatif deskriptif korelasional. Lokasi penelitian ini adalah Lembaga RA (Raudhatul Athfal) di Kecamatan Baleendah Kabupaten Bandung. Populasi pada penelitian ini sebanyak 265 guru dari 55 lembaga RA. Kemudian, diambil sampel dengan taraf kesalahan 5% menggunakan teknik solvin berjumlah 159 guru. Teknik pengumpulan data yang digunakan yaitu obeservasi, kuesioner, dan dokumentasi. Validasi instrumen menggunakan rumus korelasi product moment dan uji reliabilitas menggunakan rumus Alpha Cronbach. Teknik analisis data menggunakan teknik kategorisasi untuk pemetaan kompetensi pedagogik ditinjau dari kualifikasi akademik, dan teknik korelasi Product Moment untuk mencari hubungan kedua variabel. Hasil analisis deskriptif menunjukkan bahwa guru yang memiliki kompetensi pedagogik dengan kategori sedang yaitu sebanyak 101 guru (63,5%), 30 guru (18,9%) dalam kategori tinggi, dan 28 guru (17,6%) dengan kategori rendah. Terdapat adanya hubungan positif yang signifikan antara kualifikasi akademik dengan kompetensi pedagogik guru RA Kecamatan Baleendah Kabupaten Bandung. Berdasarkan hasil penelitian, maka dapat disimpulkan bahwa kompetensi pedagogik guru RA di Kecamatan Baleendah Kabupaten Bandung berada pada kategori sedang (63,5%) dan terdapat adanya hubungan positif yang signifikan antara kualifikasi akademik guru dengan kompetensi pedagogik guru RA dengan tingkat sedang. Saran yang diberikan oleh peneliti yaitu: kepada para guru lembaga Raudhatul Athfal (RA) untuk meningkatkan kompetensi pedagogik guru RA dan juga meningkatkan kualifikasi akademiknya bagi guru yang belum sesuai dengan peraturan pemerintah agar memenuhi standar kualifikasi akademik yang sudah ditentukan.